Fraction transfer process in on-line comprehensive two-dimensional liquid-phase separations - Česla, Petr; Křenková, Jana (Journal of separation science, 2017)
Two-dimensional liquid-phase separations have gained increasing attention for their ability to separate complex sample mixtures. Among the experimental setups used, an on-line approach is preferred to reduce the probability of sample contamination, for easier automation and high-sample throughput. The interfacing of the separation techniques in the on-line mode brings additional demands on proper optimization of the two-dimensional system. In this review, the possibilities of the on-line coupling of liquid chromatography and liquid chromatography with capillary electrophoresis in two-dimensional systems are discussed. Special attention is paid to the fraction transfer process, which includes an overview of interfaces and experimental setups applied, the compatibility issues of separation systems, and instrumental parameters. The benefits and drawbacks of using electromigration separations in combination with liquid chromatography are presented as well.
Keywords: liquid chromatography; two-dimensional separations; Chemistry Techniques, Analytical; Chromatography, Liquid; capillary electrophoresis; fraction transfer; chromatografie kapalinová; comprehensive liquid chromatography; Electrophoresis, Capillary; chemické techniky analytické; elektroforéza kapilární